Cuisine and conquest: interdisciplinary perspectives on food, continuity and change in 11th-century England and beyond - Jervis, Ben; Whelan, Fiona; Livarda, Alexandra (Routledge, 2017)
Multiple strands of evidence are combined to determine the impact of the Norman Con-quest on food culture. Diet is reconstructed from the analysis of zooarchaeological, archaeobotanical and ceramic evidence, as well as through an analysis of the 12th-century text Urbanus magnus. This text is then examined alongside the study of artefacts to reconstruct practices surrounding cooking and dining. The chapter concludes that the Norman Conquest did not have a clear and consistent impact on food culture. Whilst some changes, particularly to elite cuisine, can be related to Norman influences, others, such as an increase in fish consumption, are in fact indicative of longer-term trends. It is considered that the continuities and changes observed caused different experiences of the Conquest to be mediated through food, for some allowing new forms of elite, Norman, identity to emerge, whilst for others the consumption of familiar foods provided stability in a changing world.